Too Early for Physics? Effect of Class Meeting Time on Student Evaluations of Teaching in Introductory Physics. - Tobin, Roger G. (Tufts University. Tisch Library., 2017)
This paper reports observations that show a significant effect of class meeting time on student evaluations of teaching for an introductory college physics class. Students in a lecture section with an early-morning meeting time gave the class and instructors consistently lower ratings than those in an otherwise nearly identical section that met an hour later, even for aspects of the course that were seemingly identical across the two sections.